Toward metrics and model validation in web-site QEM - Olsina Santos, Luis Antonio (2000)
In this work, a conceptual framework and the associated strategies for metrics and model validation are analyzed regarding website measurement and evaluation. Particularly, we have conducted three case studies in different Web domains in order to evaluate and compare the quality of sites. For such an end the quantitative, model-based methodology, so-called Web-site QEM (Quality Evaluation Methodology), was utilized. In the assessment process of sites, definition of attributes and measurements, preference criteria for elementary evaluation, and an aggregation model of attributes and characteristics for global evaluation have intervened. Hence, in the present paper, the validation framework and the theoretical validation of some used Web metrics and model for assessment purpose are discussed considering the representational theory of measurement.